Point‐of‐care detection of cytokines in cytokine storm management and beyond: Significance and challenges. Issue 4 (4th May 2021) - Liu, Guozhen; Jiang, Cheng; Lin, Xiaoting; Yang, Yang
Abstract: Cytokines are signaling molecules between cells in immune system. Cytokine storm, due to the sudden acute increase in levels of pro‐inflammatory circulating cytokines, can result in disease severity and major‐organ damage. Thus, there is urgent need to develop rapid, sensitive, and specific methods for monitoring of cytokines in biology and medicine. Undoubtedly, point‐of‐care testing (POCT) will provide clinical significance in disease early diagnosis, management, and prevention. This review aims to summarize and discuss the latest technologies for detection of cytokines with a focus on POCT. The overview of diseases resulting from imbalanced cytokine levels, such as COVID‐19, sepsis and other cytokine release syndromes are presented. The clinical cut‐off levels of cytokine as biomarkers for different diseases are summarized. The challenges and perspectives on the development of cytokine POCT devices are also proposed and discussed. Cytokine POCT devices are expected to be the ongoing spotlight of disease management and prevention during COVID‐19 pandemic and also the post COVID‐19 pandemic era. Abstract : Due to the significance of cytokines in biology and medicine, great advances have been witnessed with respect to cytokine biosensing technologies and cytokines clinical utility. With the aid of digital monitoring tools, POC detection of cytokines as biomarkers might step into new era toward disease diagnosis, prevention and management.